Strategies for maintaining a handstand in the anterior-posterior direction - Kerwin, D.; Trewartha, G. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The purpose of this analysis was to determine the contributions made by wrist, shoulder, and hip joint torques in maintaining a handstand. METHODS: Handstand balances (N = 6) executed on a force plate and recorded with two genlocked video cameras were subjected to inverse dynamics analysis to determine anterior-posterior joint torques at the wrists, shoulders, and hips. Multiple regression analyses were conducted to investigate which of the joint torques were influential in accounting for anterior-posterior whole-body mass center (CM) movement. RESULTS: Results demonstrated that, in general, all calculated joint torques contributed to CM movement. In a number of trials, wrist torque played a dominant role in accounting for CM variance. Ostensibly, superior handstand balances are characterized by important contributions from wrist torques and shoulder torques with little influence from hip torques. In contrast, hip torques were found to be increasingly influential in less successful balances. CONCLUSIONS: It is concluded that multiple joints are utilized in maintaining a handstand balance in the anterior-posterior direction, and there appears to be two joint involvement strategies, which supports similar findings from postural research on normal upright stance.